13.5k views
0 votes
Use Theorem 2.1.1 to verify the logical equivalence. Give a reason for each step. -(pv –q) v(-p^q) = ~p

1 Answer

2 votes

Answer:

The statement
\lnot(p\lor\lnot q)\lor(\lnot p \land \lnot q) is equivalent to
\lnot p,
\lnot(p\lor\lnot q)\lor(\lnot p \land \lnot q) \equiv \lnot p

Explanation:

We need to prove that the following statement
\lnot(p\lor\lnot q)\lor(\lnot p \land \lnot q) is equivalent to
\lnot p with the use of Theorem 2.1.1.

So


\lnot(p\lor\lnot q)\lor(\lnot p \land \lnot q) \equiv


\equiv (\lnot p \land \lnot(\lnot q))\lor(\lnot p \land \lnot q) by De Morgan's law.


\equiv (\lnot p \land q)\lor(\lnot p \land \lnot q) by the Double negative law


\equiv \lnot p \land (q \lor \lnot q) by the Distributive law


\equiv \lnot p \land t by the Negation law


\equiv \lnot p by Universal bound law

Therefore
\lnot(p\lor\lnot q)\lor(\lnot p \land \lnot q) \equiv \lnot p

Use Theorem 2.1.1 to verify the logical equivalence. Give a reason for each step. -(pv-example-1
User Tejasvi Hegde
by
5.6k points